Five-year outcomes with anti-vascular endothelial growth factor in neovascular age-related macular degeneration: results of the Comparison of Age-related Macular Degeneration Treatments Trials - Mathis, Thibaud; Kodjikian, Laurent (Annals of Eye Science, 2017)
Age-related macular degeneration (AMD) is the leading cause of irreversible blindness in the elderly in industrialized countries (1,2). Current treatments for AMD are severely limited and only the wet form can be treated with anti-vascular endothelial growth factor (anti-VEGF). Although anti-VEGF is a palliative treatment, this drug dramatically improves the prognosis for patients with this disease (3). For example, in a population-based study in Denmark, the incidence of legal blindness from AMD was reduced by 50% after 2006 (4). Currently, all patients diagnosed with neovascular AMD are treated with intravitreal injections of one of the three drugs available in clinical practice that target VEGF: bevacizumab, the most widely used in the USA, ranibizumab and aflibercept (5).